An Analysis of Teacher’s Technique Speaking on Class During Covid-19 at Second Grade of Junior High School - Enzelina Sinaga; Ramauli Rajagukguk; Surliyah Ningsih; Rahma Wati (Institut Agama Islam Negeri Palopo, 2021)
AbstractThe title of this research is